2020
DOI: 10.2174/1381612825666191216145153
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Melanocortin-4 Receptor by a Synthetic Agonist Inhibits Ethanolinduced Neuroinflammation in Rats

Abstract: Background: High ethanol intake induces a neuroinflammatory response resulting in the subsequent maintenance of chronic alcohol consumption. The melanocortin system plays a pivotal role in the modulation of alcohol consumption. Interestingly, it has been shown that the activation of melanocortin-4 receptor (MC4R) in the brain decreases the neuroinflammatory response in models of brain damage other than alcohol consumption, such as LPS-induced neuroinflammation, cerebral ischemia, glutamate excitotoxicity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Thus, 18 rats (62% of the starting group of rats) preferred morphine for the complete extension of the study. These rejection rates are in concordance to what was previously reported for other drugs since a diversity in the willingness to consume a drug is observed when outbred animals, i.e., not selectively bred to self-administer a drug, are used as a model for the study of consumption of ethanol [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, 18 rats (62% of the starting group of rats) preferred morphine for the complete extension of the study. These rejection rates are in concordance to what was previously reported for other drugs since a diversity in the willingness to consume a drug is observed when outbred animals, i.e., not selectively bred to self-administer a drug, are used as a model for the study of consumption of ethanol [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although we hypothesized that the activation of MC4R in the brain inhibits NF-κB activity and neuroinflammation induced by ethanol (Flores-Bastías and Karahanian, 2018;Flores-Bastías et al, 2019), MC4R elicits additional mechanisms that would help explain the effects of α-MSH or its synthetic analogs in reducing alcohol intake. After the pioneering work of Xu et al (2003) who reported that the activation of MC4R induces brain-derived neurotrophic factor (BDNF) expression in the hypothalamus, it was determined that BDNF is a downstream effector of MC4R signaling in food intake control (Nicholson et al, 2007;Bariohay et al, 2009).…”
mentioning
confidence: 99%
“…MC4R functions to regulate food intake and energy expenditure, and regulate insulin secretion, lipid metabolism, bone mineral density, and body length [[11]]. The deficiency of MC4R influences eating behaviors in humans and animals (Table 2) [[54]]. Experiments using MC4R-inactivated mice develop a maturity-onset obesity syndrome associated with hyperphagia, hyperinsulinemia, and hyperglycemia [[55]].…”
Section: Role Of α-Msh In Appetite Regulationmentioning
confidence: 99%